Knowledge, attitude, and practice associated with antimicrobial resistance among medical students between 2017 and 2022: A survey in East China - Min, Shengyi; Zhou, Yuxuan; Sun, Yuxuan; Ye, Jiaquan; Dong, Yongfei; Wang, Xichao; Zhou, Zhemin; Zhou, Hanyu; Li, Heng (Frontiers in Public Health, 2022)
This study described the knowledge, attitude, practice regarding antimicrobial resistance (AMR) among medical students between 2017 and 2022 in East China. A questionnaire-based survey was conducted with a total of 1066 respondents. We highlighted that the undergraduates had a significant increase in the knowledge of antimicrobial resistance during the five years from 2017 to 2022 (p<0.001). The majority of the assertions about the AMR were correctly identified by respondents. However, gaps were still observed in the issues of antimicrobial targets and bacterial transmission. In addition, overconfident attitudes and inappropriate behaviors of antimicrobial overuse and misuse were observed in the respondents. A number of 30.2% to 45.2% of the respondents asserted that there is no risk of AMR as long as the antimicrobials are taken correctly, and a proportion of the students (25.3% in 2022; 69.3% in 2017, p<0.001) declared to buy antimicrobials from friends or family members to treat the same illness. Finally, spearman correlation coefficient was enrolled to compare the correlation of the student’s KAP. Results showed that the students’ knowledge of antimicrobials had a correlation with attitude (p=0.0126) and practice (p<0.001), suggesting that public education on knowledge could influence the behaviors among the medical students. Taken all together, our findings show a need to strengthen the medical students’ cogitation on antimicrobial attitude and practice of appropriate usage as an essential strategy to reduce intractable public health problems. Additional curriculum reforms will be needed to add more specific AMR-related lectures to raise awareness amongst medical students in China.